BIOMECHANICAL MODELING OF BRAIN TISSUE FOR SAFER NEUROSURGICAL INTERVENTIONS: COMPUTATIONAL STRATEGIES FOR PRECISION PLANNING, DEFORMATION PREDICTION, AND INTRAOPERATIVE RISK REDUCTION (Global Conference on Medical and Health Sciences, 2026)
Biomechanical modeling of brain tissue has emerged as a critical innovation in modern neurosurgery, offering new opportunities to improve surgical safety, precision, and intraoperative adaptability. Because brain tissue undergoes continuous deformation during surgery due to gravity, cerebrospinal fluid loss, edema, retraction, and tumor resection, conventional navigation systems based solely on preoperative imaging may lose accuracy over time. Computational biomechanical models provide a dynamic framework for predicting tissue displacement, estimating brain shift, and supporting safer surgical decision-making.
Keywords: Biomechanical modeling; Brain tissue; Neurosurgery; Brain shift; Finite element analysis; Surgical planning; Intraoperative navigation; Computational biomechanics; Safer intervention; Precision surgery